COVID-19 Pandemic Preparedness in Egypt's Teaching Hospitals: A Needs Assessment Study - Abd El Ghaffar, Muhammad Mostafa; Salem, Marwa Rashad; Al Soda, Mohamed Fawzy; Abd El Razik, Madiha Said; Tahoon, MarwAli Hassab; Tahoon, Mohamed Fathy; Eysa, Basem; Hegazy, Abd Elfattah Elsayed; Eleraky, Abdelkarem Emam; Eltayar, Ayman A.; Eldarandly, Wael Mahmoud Hossam El Din; Omran, Dalia (Frontiers in Public Health, 2022)
Introduction: Regular collection and monitoring of data describing the dynamics of the utilization of healthcare services, especially in teaching hospitals (TH) (which provide model quality medical services) are critical for COVID-19 pandemic preparedness. Methods: Analysis of data and information derived from service statistics reports in terms of hospital resources, as well as utilization patterns of beds, ICU, and ventilators for eleven screening hospitals affiliated with the General Organization of Teaching Hospital and Institutes in Egypt assigned by the Ministry of Health and Population to provide medical care for COVID-19 patients. The study covers the period from June 1st to July 15th, 2020. We computed hospital indicators in terms of COVID-19 screening services as well as utilization patterns of inpatient beds, ICU beds, and ventilators. Results: A total of 78,869 patients and 2,176 medical staff patients were presented with COVID-19 triage symptoms. Screening tests conducted in the targeted 11 hospitals delineated that 22.2% of patients and 27.9% of medical staff members were COVID-19 PCR-confirmed cases. Bed occupancy rate was 70% for patients and 67% for medical staff patients. For ICU, the bed occupancy rate was 92 % for inpatients and 88% for medical staff patients. Among the confirmed cases, 38% of inpatients utilized a ventilator versus 36% of medical staff cases. Hospital ranking according to utilization pattern, Hospital H ranked first in terms of high load of screening services. Hospital C ranked first regarding the number of confirmed cases, whereas Hospital D ranked first for high ICU utilization among all teaching hospital ICU cases. With respect to medical staff, Hospital H ranked first for the high load of screening services for the total studied cases. Hospital B ranked first for the number of confirmed cases. Hospital G ranked first regarding high ICU utilization among all teaching hospital ICU cases Conclusion: Teaching hospitals have demonstrated preparedness for the COVID-19 pandemic by maintaining bed occupancy rate of 70% or less and ventilator utilization at less than 40% of confirmed cases. However, the bed occupancy rate was more than 90% indicating a shortage of resources.